2008
DOI: 10.1016/j.iccn.2008.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Intensive care nurses’ encounters with multicultural families in Norway: An exploratory study

Abstract: SummaryThe aim of this study was to explore nurses' perceptions of their encounters with multicultural families in intensive care units in Norwegian hospitals. Immigrants from non-Western countries make up 6.1% of the population in Norway. When a person suffers an acute and critical illness the person's family may experience crises. Nurses' previous experiences of caring for culturally diverse patients and families is challenging due to linguistic differences, and contextual factors. Family members should be n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 20 publications
0
43
0
Order By: Relevance
“…They struggle to take care of and protect their own cultural traditions in the context of a western medical model and interaction with the nurses in the ICU. Reflecting on their experiences with culturally diverse family members, intensive care nurses themselves described events as challenging and somewhat ambiguous (Høye and Severinsson, 2008). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They struggle to take care of and protect their own cultural traditions in the context of a western medical model and interaction with the nurses in the ICU. Reflecting on their experiences with culturally diverse family members, intensive care nurses themselves described events as challenging and somewhat ambiguous (Høye and Severinsson, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…ICU nurses have expressed concerns about the potential disruption caused by large family groups fulfilling a cultural obligation to gather during a health crisis (Høye and Severinsson, 2008). With regard to other traditions, the participants reported that the nurses were sensitive to multicultural families' religious symbols, headwear and rituals and thus seemed to meet their expectations and wishes.…”
Section: Discussionmentioning
confidence: 99%
“…Language barriers, inadequate translation, and mistrust precipitated by lack of explanation from the nurse created emotional stress for the parents [26]. Families verbalized in the posthospital experience that if the nurses had informed them of visiting policies early on, they would have been able to function within the rules more appropriately [21]. Parents of NICU patients from this study suggest strategies for improving communication and decreasing stress as follows: answer questions carefully, teach by demonstration, take time to explain in simple English, set up an environment of trust so that families feel “safe” to ask questions [46].…”
Section: Methodsmentioning
confidence: 99%
“…The manifest content analysis pertained to what both the healthcare professionals and the patients expressed; whereas, the latent content analysis pertained to the meaning of what they stated. Examples of related research are Granerud and Severinsson, 20 Høye and Severinsson, 21 Nystedt et al 22 The second manner analyzes manifest content, exemplified by Hök et al 23 They identified, coded and sorted into categories without meaning analysis. The third manner analyzes latent content, exemplified by Gustafsson et al 24 They explored older people's body experiences, developing meaning units, condensed meaning units, and themes, without explicit categorization.…”
Section: Data Analysis and Conceptual Developmentmentioning
confidence: 99%